2018
DOI: 10.1515/nanoph-2017-0135
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous temperature coefficient of resistance in graphene nanowalls/polymer films and applications in infrared photodetectors

Abstract: Graphene nanowalls (GNWs) exhibit outstanding optoelectronic properties due to their peculiar structure, which makes them a great potential in infrared (IR) detection. Herein, a novel IR detector that is composed of polydimethylsiloxane (PDMS) and designed based on GNWs is demonstrated. Such detector possesses an anomalous temperature coefficient of resistance of 180% K −1 and a relatively high change rate of current (up to 16%) under IR radiation from the human body. It primarily attributes to the ultra-high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…The strong nonlinear behavior resulted from the temperature-sensitive interconnection among graphene flakes [51]. In the literature, it was found that the temperature coefficient of resistance of graphene nanowall-polymer films changed from around 6%/K at 25 • C to 180%/K at 40 • C due the thermal strain effect [64]. Thus, the strain effect on CNTs is expected to contribute to the higher TCR of the CNT-MoS 2 composite network.…”
Section: Thermal Properties and Temperature Sensitivitymentioning
confidence: 99%
“…The strong nonlinear behavior resulted from the temperature-sensitive interconnection among graphene flakes [51]. In the literature, it was found that the temperature coefficient of resistance of graphene nanowall-polymer films changed from around 6%/K at 25 • C to 180%/K at 40 • C due the thermal strain effect [64]. Thus, the strain effect on CNTs is expected to contribute to the higher TCR of the CNT-MoS 2 composite network.…”
Section: Thermal Properties and Temperature Sensitivitymentioning
confidence: 99%
“…The sensors were responsive despite being insulated with an overlying layer as protection against all these environmental variations. Graphene nano-wells show tremendous temperature coefficients of resistance (i.e., 180% K −1 ), which is an interesting development for the detection of human body temperature [ 129 ]. A biocompatible conductive green electrolyte is another attractive candidate for in vivo and in vitro body temperature measurements [ 46 ].…”
Section: Wearable Sensorsmentioning
confidence: 99%
“…VOG, a vertical structure formed by the overlap of longitudinally grown graphene films, not only possesses similar electrical characteristics as graphene films but also exhibits excellent light absorption from the near-infrared (NIR) to infrared (IR) region because of the edge effects and uniform index of refraction at the interface. The unique structural/electrical properties of VOG are advantageous to the transport of photo-generated carriers and decrease recombination on the surface . Direct growth of VOG on arbitrary substrates by plasma-assisted chemical vapor deposition (PACVD) ensures the high quality of Schottky junction and improves the device performance. , Besides, GQDs as a novel class of carbon nanomaterials have undergone tremendous development in the past few years because of the unique electronic, optical, and chemical properties in conjunction with quantum confinement and edge effects. , Compared to traditional graphene derivatives, the enhanced solubility of GQDs is ideal for solution processing, thus boosting the production yields.…”
Section: Introductionmentioning
confidence: 99%
“…17−19 The unique structural/ electrical properties of VOG are advantageous to the transport of photo-generated carriers and decrease recombination on the surface. 20 Direct growth of VOG on arbitrary substrates by plasma-assisted chemical vapor deposition (PACVD) ensures the high quality of Schottky junction and improves the device performance. 18,21 Besides, GQDs as a novel class of carbon nanomaterials have undergone tremendous development in the past few years because of the unique electronic, optical, and chemical properties in conjunction with quantum confinement and edge effects.…”
Section: ■ Introductionmentioning
confidence: 99%